Soils & Fertilizers for Master Gardeners: Organisms in the Soil - Amy L. Shober (EDIS)
Revised! SL-271, a 3-page illustrated fact sheet by Amy L. Shober, discusses different types of organisms and their impact on the soil environment. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Science, January 2009.